Detection of IgE autoantibodies to BP180 and BP230 and their relationship to clinical features in bullous pemphigoid. (12th April 2017) - Hashimoto, T.; Ohzono, A.; Teye, K.; Numata, S.; Hiroyasu, S.; Tsuruta, D.; Hachiya, T.; Kuroda, K.; Hashiguchi, M.; Kawakami, T.; Ishii, N.
Summary: Background: IgE autoantibodies are considered to be involved in the pathogenesis of bullous pemphigoid (BP), particularly inflammatory and erythematous phenotypes. Objectives: To develop reliable enzyme‐linked immunosorbent assays (ELISAs) for the detection of IgE autoantibodies to both BP180 and BP230 in BP sera, and to compare the ELISA results with clinical features. Methods: We used commercially available IgG ELISAs to develop IgE ELISAs for both BP180 and BP230. To determine the influence of excess amounts of IgG autoantibodies, all normal and BP sera were tested before and after IgG adsorption. The results of the IgE ELISAs were statistically compared with various ELISAs and various clinical parameters, including our own severity scores and BP phenotypes. Results: IgG adsorption generally showed no changes in sensitivity and specificity for IgE ELISAs, although slight cross‐reactivity of anti‐IgE secondary antibody to IgG and interference of excess amounts of IgG autoantibodies to IgE reactivity were suggested. IgE autoantibodies to BP180 were found in 21 of 36 BP sera and IgE autoantibodies to BP230 were found in 18 of 36 BP sera. The results of IgG and IgE ELISAs for both BP180 and BP230 were well correlated. IgG and IgE anti‐BP180 antibodies correlated with disease activity but IgG and IgE anti‐BP230 autoantibodies did not. IgE anti‐BP230 autoantibodies correlated with nodular phenotype but not erythematous phenotype. Conclusions: The results of this study indicated that IgE autoantibodies to both BP180 and BP230 are frequently detected in BP sera. IgE anti‐BP180 autoantibodies seemed to be pathogenic, while an association between IgE autoantibodies and inflammatory BP phenotype was not indicated. Abstract : What's already known about this topic? Although recent studies have indicated that IgE autoantibodies are frequently detected in bullous pemphigoid (BP), in addition to IgG autoantibodies, their diagnostic and pathogenic relevance have not been fully documented. Reliable IgE enzyme‐linked immunosorbent assays (ELISAs) for BP antigens, particularly BP230, have not been established. What does this study add? This study establishes reliable diagnostic IgE ELISAs for both BP180 and BP230, in which the influence of excess amounts of IgG autoantibodies was extensively determined. This study confirms the frequent detection of IgE autoantibodies to BP180 and BP230. IgE autoantibodies to BP180 correlated with disease activity, and IgE anti‐BP230 antibodies correlated with nodular phenotypes, while they were not correlated with the inflammatory erythematous phenotype. What is the translational message? We have developed reliable IgE ELISAs for both BP180 and BP230, which can be used in clinical practice. This study suggests that titres of IgE anti‐BP180 autoantibodies correlated with disease activity in BP and should be clinically useful for selecting the best treatment, particularly with regard to anti‐IgE antibody therapy. Linked Comment: Hammers and Payne. Br J Dermatol 2017;177 :13–14